A comprehensive combustion, performance, and environmental analyses of algae biofuel, hydrogen gas, and nano-sized particles (liquid-gas-solid mix) in agricultural CRDI engines - Venu H.; Kiong T.S.; Soudagar M.E.M.; Razali N.M.; Ramesh S.; Fouad Y.; Rajabi A.; Appavu P.; Raju V.D.; Veza I.; Subrmani L.; Kalam M.A.; et al. (Elsevier Ltd, 2025)
The present research encompasses the utilization of TiO2 nano particles with enrichment of H2 (10 lpm) with Chlorella Emersonii Methyl Ester (CEME) on an agricultural-based CRDI engine. CEME20 (20% chlorella emersonii methyl ester blended with 80% mineral diesel) is employed for the tests. The nanoparticle concentration is limited to 50 ppm which has been considered according to O2 concentration in biodiesel. Experimentation revealed that, with hydrogen gas and TiO2 nanoparticles, the BTE and BSFC were improved significantly. At full load conditions, BTE is enlarged by 7.3%. In addition, there is a simultaneous decrease in HC and CO emissions (by about 36.3 and 40.9% respectively) for algal biofuel blends, while NOx emissions increased by 27.3% with respect to mineral diesel. 5.1% and 6.5% increase in combustion characteristics (79.8 bar combustion pressure and 89.2 J/CA heat release rate)were observed for the CEME/H2/TiO2 blend which could be attributed to effective combustion of hydrogen and catalytic combustion activity provided by TiO2 nano additives. CEME/H2/TiO2blend recorded maximum Mass Fraction burnt (MFB) (74.7%) as well as lowered PSD (Particle size Diameter) profile (34.8 nm @ 0.29 E+08 dN/dlogDp (#/cm3)) at full engine load condition indicating the presence of H2 and nano additives which has influence over the combustion. ? 2024 Hydrogen Energy Publications LLC